Rapid Detection of Extended-Spectrum β-Lactamases (ESBL) and AmpC β-Lactamases in Enterobacterales: Development of a Screening Panel Using the MALDI-TOF MS-Based Direct-on-Target Microdroplet Growth Assay - Correa-Martínez, Carlos L.; Idelevich, Evgeny A.; Sparbier, Katrin; Kostrzewa, Markus; Becker, Karsten (Frontiers in Microbiology, 2019)
Introduction Antibiotic resistant bacteria are a growing concern worldwide. Extended-spectrum β-lactamases (ESBL) represent the most common resistance mechanism of Gram-negative bacteria against β-lactams, underlining the need for adequate diagnostic methods that provide reliable information in the shortest time possible. AmpC, a less prevalent but increasingly relevant class of β-lactamases, pose an additional challenge as their detection is complex. Here, we present an ESBL and AmpC screening panel employing the MALDI-TOF MS-based direct-on-target microdroplet growth assay (DOT-MGA). Materials and Methods Four reference strains recommended by the European Committee on Antimicrobial Susceptibility Testing (EUCAST) were used to develop the panel, which was further validated on 50 clinical Enterobacterales isolates resistant to third generation cephalosporins. The panel relies on the synergistic effect between ESBL and/or AmpC β-lactamase inhibitors and cephalosporins, which indicates β-lactamase production. Microdroplets containing the tested microorganism, cephalosporins in different concentrations and inhibitors were pipetted onto an MBT Biotarget and incubated for 3 or 4 hours at 35 ± 1 °C. Afterwards, the liquid medium was removed and the material adhered to the spots was analyzed by MALDI-TOF MS. Synergy was detected by determining and comparing the minimum inhibitory concentrations of the tested cephalosporins with and without β-lactamase inhibitors. Data were interpreted following a diagnostic algorithm proposed by EUCAST in order to establish a final diagnosis. In comparison, PCR, broth microdilution (BMD) and combination disk tests (CDT) were performed. Results Compared to the PCR results, the following positive and negative percent agreement values (PPA/NPA) were obtained for each resistance mechanism: ESBL, 94.44%/100%; AmpC, 94.44%/93.75% and ESBL+AmpC, 100%/100%. These results, obtained after 4 hours of incubation, were comparable with those of BMD and showed a higher accuracy than CDT. Discussion We propose a novel phenotypic method for detection of ESBL and AmpC β-lactamases in Enterobacterales that provides reliable results in a short time, representing a promising alternative to the diagnostic techniques currently available. This easy-to-perform approach has potential for being implemented in routine laboratories, contributing to the further diversification of mass spectrometry technology into other fields such as antibiotic resistance testing.